Data Sharing and Engineering Faculty: An Analysis of Selected Publications. Issue 4 (2nd October 2018) - Wiley, Christie
ABSTRACT: Funding agency mandates have issued memorandums requiring applicants to submit a data management plan as well as the inclusion and support for public access to research data. This inclusion and access indicates growing trends among journal publishers. This article examines twenty-eight engineering journal research data policies to better understand the current state of data sharing, the relationship to open access, how data are shared with supplementary files, and how can we measure if the strength of data-sharing policies influences the observed pervasiveness of sharing data. The purpose of this study is to determine the pervasiveness and quality of data-sharing policies as reflected in editorial policies and the instructions to authors. Examining engineering journals scholarly communication policies provides an opportunity for data librarians to review and anticipate new data trends, opportunities, and challenges, to adjust library services, and adjust user expectations or negative preconceptions.